Impact of adherence to media reporting guidelines in suicide news-focused Instagram posts by Malaysian news media organisations - A study on user responses - Eldeen Husaini, Amirun Haqqim (2024)
Adherence to media reporting guidelines on suicide news reporting has been found to be an effective population-level prevention strategy for suicidal behaviours. Nevertheless, media professionals encounter several challenges when attempting to implement these guidelines in their work. These challenges can be attributed to the limited research available on how to effectively integrate these guidelines into journalistic practices, and the absence of compelling evidence supporting their efficacy in reducing population-level suicidal behaviours. This need for more research on the significance of adhering to media reporting guidelines is particularly relevant in the context of social media and within Southeast Asian countries. To address this gap, the present study aimed to examine the nature of suicide news reporting on Instagram by Malaysian news media organisations and to explore the user sentiments expressed by audiences in relation to such content. The study conducted a series of content analyses and sentiment analyses on the posts and comments associated with ten Instagram accounts officially affiliated with prominent Malaysian news media organizations. The findings of the study indicate that within these accounts, there is a greater prevalence of suicide news-focused Instagram posts that generally adhere to media reporting guidelines compared to those that did not adhere to these guidelines. Furthermore, the analysis revealed various distinguishing features between posts that adhered strongly to media reporting guidelines and those that adhered less rigorously. Additionally, the analysis on audience sentiments within the comments found support for the importance of adherence to media reporting guidelines by Malaysian news media organizations when covering suicide news-related topics. This study delves into the nature of adherence to media reporting guidelines within suicide.